GAMBARAN MANAJEMEN COMPLAIN DI RSUP DR. TADJUDDIN CHAILD MAKASSAR PROVINSI SULAWESI SELATAN - Tri Wahyudi; Ana Lestari (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2022)
One of the conditions that shows the problem of service quality in hospitals is a complaint from the targeted health service users are the attitudes and actions of doctors, nurses, administration and service sustainability, drug supplies, inadequate infrastructure and medical equipment. The purpose of this study was to determine the effect of complaint handling on the loyalty of BPJS patients in the Hospital Inpatient Installation. dr. Tadjuddin Chalid Makassar . This type of research used in this study is quantitative descriptive research. This study was conducted in an inpatient installation of RSUP. dr. Tadjuddin Chalid Makassar as many as 200 respondents determined through accidental sampling technique. The data in this study were obtained through questionnaires and secondary hospital data. The results showed that there is a picture of complaint management in RSUP. dr. Tadjuddin Chalid Makassar is already very good with a Mean score of 22, but needs improvement in handling complaints, such as the response time of the complaint and the media provided to make the complaint.